Determinan Kualitas Laba Sektor Industri: Persistensi Laba, Peluang Pertumbuhan, Perataan Laba dan Peluang Investasi - Febri Rahmi; Elfiandri (Universitas Muhammadiyah Jakarta, 2026)
Objectives: Earnings information is important for investors and creditors in decision-making because it reflects the stability and sustainability of a company’s performance. High-quality earnings can reduce risk and uncertainty and are reflected in stock prices. This study aims to analyze the effects of earnings persistence, growth opportunities, income smoothing, and the investment opportunity set (IOS) on earnings quality. Design/methodology/approach: This study employed a quantitative approach using a sample of 25 industrial sector companies listed on the Indonesia Stock Exchange during 2021–2024. Purposive sampling resulted in 100 observations. The data were analyzed using multiple linear regression with EViews. Results/findings: Growth opportunities have a significant effect on earnings quality, whereas earnings persistence, income smoothing, and IOS have no significant effect. Theoretical contribution: This study extends the literature by showing that earnings quality is also influenced by factors beyond earnings characteristics and investment opportunities. Practical contribution: The findings encourage investors and management to assess and improve earnings quality through high-quality financial reporting and good corporate governance. Limitations: This study is limited to industrial sector companies and the four examined determinants.